2012
DOI: 10.1504/ijse.2012.047932
|View full text |Cite
|
Sign up to set email alerts
|

Rule of law and the environmental Kuznets curve: evidence for carbon emissions

Abstract: In response to recently growing literature investigating the relationship between environment and institutions, this study investigates how rule of law influences the level of income at the turning point of the Environmental Kuznets Curve (EKC). Using an alternative specification of EKC that avoids nonlinear transformation of potentially nonstationary regressors, investigated by Bradford et al. (2005) and Leitão (2010), we find the evidence for the EKC in European countries for carbon emissions. Our results fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Although some studies take into account the rule of law [23][24][25], to the best of our knowledge, there are very few works [26,27,15] that analyze this institution from an environmental perspective. As for the choice of the pollutant, we concentrate our attention to carbon dioxide, which is one of the most considered energy-related pollutant and a major source of the greenhouse effect.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies take into account the rule of law [23][24][25], to the best of our knowledge, there are very few works [26,27,15] that analyze this institution from an environmental perspective. As for the choice of the pollutant, we concentrate our attention to carbon dioxide, which is one of the most considered energy-related pollutant and a major source of the greenhouse effect.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on general innovation states that better institutions are likely to promote general innovation and investments (Habiyaremye and Raymond 2013;Tebaldi and Elmslie 2013;Silve and Plekhanov 2015). The contributions focussing on the relationship between institutions and the environment suggest that good governance is generally associated with a greater adoption of environmental policies and with better environmental outcomes (Castiglione et al 2012(Castiglione et al , 2014.…”
Section: Hypothesis 2 (H2): Institutional Quality Measured As Good Gmentioning
confidence: 99%
“…One of these factors is institutional enforcement. Institutions, such as the protection of property rights, legal origins, democracy and governance, have been shown to have a strong impact on the quality of the environment [10][11][12][13][14]. However, among the institutions studied from an environmental perspective, that of the rule of law has not yet received the attention it deserves.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental policies are therefore dependent on the quality of this institution, as it determines their effective application. Although the link between the quality of the rule of law and effective environmental policies is hardly surprising, very few empirical studies have shown that the rule of law improves environmental quality [13,22,27].…”
Section: Introductionmentioning
confidence: 99%